Electrospun Fibers of Poly (Lactic Acid) Containing Bioactive Glass and Magnesium Oxide Nanoparticles for Bone Tissue Regeneration - Zapata-Ramirez, P; Canales-Arévalo, D; Reyes-Lopez, F; Saavedra-Gonzalez, M (Elsevier B.V., 2022)
Electrospun fibers of poly (lactic acid) (PLA) containing 10 and 20 wt% of bioactive glass (n-BG) and magnesium oxide (n-MgO) nanoparticles of ca. 27 and 23 nm respectively, were prepared toward to application in bone tissue engineering. The addition of both nanoparticles into the PLA will produce a synergic effect increasing its bioactivity and antimicrobial behavior. Neat PLA scaffold and the composites with MgO showed an average fiber diameter of 1.7 ± 0.6 μm, PLA/n-BG and PLA/n-BG/n-MgO fibers presented a significant diameter increase reaching values of ca. 3.1 ± 0.8 μm. Young s modulus of the electrospun scaffolds was affected by the direct presence of the particle and scaffold morphologies. All the composites having n-BG presented bioactivity through the precipitation of hydroxyapatite structures on the surface. Although n-MgO did not add bioactivity to the PLA fibers, they were able to render antimicrobial characteristics reducing the S. aureus viability around 30%, although an effect on E. coli strain was not observed. PLA/n-BG nanocomposites did not display any significant antimicrobial behavior. The different composites increased the alkaline phosphatase (ALP) expression as compared with pure PLA barely affecting the cell viability, meaning a good osteoblastic phenotype expression capacity, with PLA/n-BG presenting the highest osteoblastic expression. © 2022 Elsevier B.V.